Greenhouse gas emissions from soils of a long-term trial in Western Kenya - Sommer, Rolf; Kihara, Job Maguta; Bolo, Peter Omondi; Kinyua, Michael (International Center for Tropical Agriculture, 2019)
Four seasons of N2O and CO2 emission from four selected treatments of CIAT’s long-term trial INM3 located in Western Kenya